Mahanimbine Improved Aging-Related Memory Deficits in Mice through Enhanced Cholinergic Transmission and Suppressed Oxidative Stress, Amyloid Levels, and Neuroinflammation - Vasudevan Mani; Nur Syamimi Mohd Azahan; Kalavathy Ramasamy; Siong Meng Lim; Abu Bakar Abdul Majeed (Brain Sciences, 2021)
Murraya koenigii leaves contain mahanimbine, a carbazole alkaloid, reported with improving cholinergic neuronal transmission and reducing neuroinflammation in the CNS. The current research investigated the effects of mahanimbine on age-related memory deficits, oxidative stress, cholinergic dysfunction, amyloid formation, and neuroinflammation in aged mice (16 months old). Mahanimbine was administered (1 and 2 mg/kg, p.o.) daily to groups of aged mice for 30 days. The Morris water maze (MWM) task was performed to study spatial learning (escape latency (EL) and swimming distance (SD)) and memory (probe test). The levels of malondialdehyde (MDA), glutathione (GSH), acetylcholine (ACh), acetylcholinesterase (AChE), β-amyloid (Aβ1-40 and Aβ1-42), β-secretase (BACE-1), as well as neuroinflammation markers (total cyclooxygenase (COX) and COX-2 expression), were measured from the isolated brain. Mahanimbine reduced the EL time and SD in the MWM test. From the probe trial, the mahanimbine-treated group spent more time in the targeted quadrant related to the age-matched control, which indicated the enhancement of memory retention. From the biochemical tests, the treatment decreased MDA, AChE, Aβ1-40, and Aβ1-42, BACE-1, total COX activity, and COX-2 expression. It also raised the brain GSH and ACh levels in aged mice compared to age-matched control. These results have supported the reversal of memory dysfunctions by mahanimbine in aged mice and hypothesized that it could be a potential target to treat age-related neurodegenerative disease.